Impact of two distinct dental anesthesia simulation models on the perception of learning by students = Impacto de dos distintos modelos de simulación para anestesia dental en la percepción del aprendizaje en estudiantes - Merino Parra, Jadith
We evaluated an infiltration anesthesia simulation model (IAM) and a conduction anesthesia simulation model (CAM) on the perception of learning by Mexican dental students. Our aim was to compare the perception of learning by dental students trained with two distinct dental anesthesia simulation model (DASM) with dental students who were not trained with a DASM. 3 groups participated in the study: G1 (N=12 students) learned to block the mental nerve (BMN) by participating in a theoretical lecture (stage 1) and a clinical demonstration (stage 2); G2 (N=12 students) learned the BMN by participating in the stage 1, stage 2, and training with the CAM; G3 (N=12 students) learned the BMN by participating in the stage 1, stage 2, and training with the IAM. The groups performed the BMN in a clinical exercise. Working-time of all participants was timed. Perception of learning for all participants was evaluated with a 5-point Likert Scale. The results showed that statistically significant differences were found between score of G1 and score of G2 and score of G3 (P<0.05). No statistically significant differences were found between scores of G2 and scores of G3. G1, G2 and G3 showed an average working-time of 12:42 minutes, 9.75 minutes and 8:03 minutes, respectively (P<0.05). We concluded that the IAM and CAM showed a positive impact on the perception of learning, and the students trained with the IAM showed a shorter working time compared with the students trained with the CAM.